Teachers' perception of the characteristics of an evidence-informed school: initiative, supportive culture, and shared reflection. Issue 4 (2nd October 2022) - Ion, Georgeta; Sirvent, Ernest López
ABSTRACT: The article analyses the characteristics of schools according to the perception teachers have regarding their commitment to using research evidence within their practice. A questionnaire focused on issues such as the use of research evidence to improve schools, as well as factors known to influence this practice, such as organizational culture, leadership style, interpersonal relationships, and decision-making processes, was administered to a sample of 462 teachers from 204 primary schools in two Spanish autonomous regions. The questionnaire responses were analysed using a two-stage factor analysis. Three clusters of schools were identified. Although teachers from a large number of schools were enthusiastic regarding the use of research evidence, others were sceptical, and most declared themselves undecided. In all cases, we observed that organizational commitment to the use of research evidence, leadership support, and debate regarding decisions were significant characteristics of those schools oriented towards the use of research evidence.